A study on the effects of the continuing rise of malls and megastores on the small grocery and dry goods store in the Chinatown of Iloilo - Lavega, Marilou P.
Basic needs and wants create demand. Demand in turn creates market. market is composed of different players, big and small, competing with each other for the acceptance of consumers or buyers. In some instance, a well-placed seller could anytime be displaced with a new entrant of big sophisticated seller. The effect could be good, other times could be unhealthy. The study on Chinatown, once known as the center of business in Iloilo City, focuses on the effect of the emergence of big market players in groceries and dry goods in the local market. The study was guided by three (3) objectives and four (4) hypotheses which will be proven if truo or not. With 35 respondents from the area, responses on their awareness were recorded thru questionnaires given out. The researchers made use of some of the previous studies and concepts to aid in analyzing and arriving of buyers in the market. Based on the gathered responses, the streets of J.M. Basa, Iznart and Aldeguer has been experiencing the impact of the increasing numbers of malls and big department stores since their (malls and department store) establishment. For the past years, and until now, there is a continuous movement of customers from the Chinatown area to the lls and megastores which greatly affected the sales performance and the income of almost all of the businesses in the chinatown. With the presence of strong competitors' threats, the owner or manager of the stores understudy launched several strategies which are discussed in this paper.